Persistent Microvascular Obstruction After Myocardial Infarction Culminates in the Confluence of Ferric Iron Oxide Crystals, Proinflammatory Burden, and Adverse Remodeling. (November 2016) - Kali, Avinash; Cokic, Ivan; Tang, Richard; Dohnalkova, Alice; Kovarik, Libor; Yang, Hsin-Jung; Kumar, Andreas; Prato, Frank S.; Wood, John C.; Underhill, David; Marbán, Eduardo; Dharmakumar, Rohan
Abstract : Background—: Emerging evidence indicates that persistent microvascular obstruction (PMO) is more predictive of major adverse cardiovascular events than myocardial infarct (MI) size. But it remains unclear how PMO, a phenomenon limited to the acute/subacute period of MI, drives adverse remodeling in chronic MI setting. We hypothesized that PMO resolves into chronic iron crystals within MI territories, which in turn are proinflammatory and favor adverse remodeling post-MI. Methods and Results—: Canines (n=40) were studied with cardiac magnetic resonance imaging to characterize the spatiotemporal relationships among PMO, iron deposition, infarct resorption, and left ventricular remodeling between day 7 (acute) and week 8 (chronic) post-MI. Histology was used to assess iron deposition and to examine relationships between iron content with macrophage infiltration, proinflammatory cytokine synthesis, and matrix metalloproteinase activation. Atomic resolution transmission electron microscopy was used to determine iron crystallinity, and energy-dispersive X-ray spectroscopy was used to identify the chemical composition of the iron composite. PMO with or without reperfusion hemorrhage led to chronic iron deposition, and the extent of this deposition was strongly related to PMO volume ( r >0.8). Iron deposits were found within macrophages as aggregates of nanocrystals (≈2.5 nm diameter) in the ferric state. Extent of iron deposits was strongly correlated with proinflammatory burden, collagen-degrading enzyme activity, infarct resorption, and adverse structural remodeling ( r >0.5). Conclusions—: Crystallized iron deposition from PMO is directly related to proinflammatory burden, infarct resorption, and adverse left ventricular remodeling in the chronic phase of MI in canines. Therapeutic strategies to combat adverse remodeling could potentially benefit from taking into account the chronic iron-driven inflammatory process. Abstract : Supplemental Digital Content is available in the text.